Paleoeskimo Demography and Sea-Level History, Kent Peninsula and King William Island, Central Northwest Passage, Arctic Canada - Dyke, Arthur S.; Savelle, James M. (ARCTIC, 2009)
Surveys on the Kent Peninsula and King William Island in the central Canadian Arctic in 2006 documented 546 Paleoeskimo dwelling features spanning about 3800 years (4500–800 14C years BP), essentially the time span of the Paleoeskimos in the region. Feature elevation above sea level, corroborated by a series of radiocarbon dates, appears to indicate that Paleoeskimo occupation passed through a series of boom-and-bust cycles, the first being the most prominent. Following the first peopling about 4500 14C years BP, populations rose to their all-time maximum between about 4200 and 3600 14C years BP. This rise was followed by a dramatic crash: a pattern that parallels histories previously documented both west and east of the region. A slight recovery between 3100 and 2500 14C years BP was temporary, and a final slight recovery between 2000 and 800 14C years BP was followed by the disappearance of the Paleoeskimos. No compelling evidence yet points to the cause of the population crashes; climate change and resource over-exploitation, acting alone or in concert, are equally plausible at this time. Dispersed nuclear families or small extended families characterized Paleoeskimo settlement patterns for most of the year in this region, as elsewhere, but annual aggregations probably involved 100 or more people. Minimal social units do not appear to have changed during seasonal aggregations in Pre-Dorset times. By Dorset times (after 2500 14C years BP), however, minimal social units at times appear to have melded together to form one or a few larger units living in one or several large dwellings. The latter may represent the social precursor of later Dorset longhouse aggregations. The persistent difference in average dwelling size between the Kent Peninsula sites and those on King William Island remains unexplained. Des levés de la presqu’île Kent et de l’île du Roi-Guillaume dans le centre de l’Arctique canadien réalisés en 2006 ont permis de répertorier 546 détails d’habitations paléoesquimaudes s’étendant sur environ 3 ...